ANALYSIS ON THE COLLOCATION TYPES FOUND IN NOVEL PERCY JACKSON AND THE OLYMPIANS “THE BATTLE OF LABYRINTH” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This research goal includes analyzing types of collocation in "The Battle of the Labyrinth," a novel by Percy Jackson & The Olympians. To decipher the type of collocation used. Scientists rely on O'Dell and McCarthy’s theory of collocations and dictionaries of collocations to find answers to the posed research questions. This study uses a qualitative research design with descriptive language. Rick Riordan is in charge of the direction. There was a sentence in Rick Riordan's film adaptation of Percy Jackson and the Olympians: The Battle of the Labyrinth that contained collocations. These are the steps that the researchers took to analyze the data they gathered: First, the researchers used Google to find and download "The Battle of Labyrinth" by Brandon Sanderson. Second, Read the whole novel carefully and repeatedly to find collocations. Third, Identifying all collocations for analysis in the novel. Fourth, Gathering all collocations as research data.. As in discussion in chapter two, Michael McCarty and Felicity O’Dell’s theory (2008) explain six types of collocation they are: Adjectives and Nouns, Nouns and Verbs or Verbs and Nouns, Noun + Noun, Verbs and expressions with preposition, Verbs and Adverbs, Adverbs and Adjectives the writer discusses one by one based on the data found. all O’Dell and McCarthy’s six types of collocation are found. Those six types of collocation are verb + adverb (75%), noun + noun (15%), noun + preposition (5%), verb + noun (5%), adjective + noun (0%), and adverbs+ adjective (0%). Then the verb + adverb and noun + noun are the most-used type of collocation found in Novel Percy Jackson and the Olympians “The Battle of the Labyrinth”.